2020
DOI: 10.4103/meajo.meajo_106_18
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography angiography and multifocal electroretinogram findings in paracentral acute middle maculopathy

Abstract: Paracentral acute middle maculopathy (PAMM) is an optical coherence tomography (OCT) finding seen in patients with retinal capillary ischemia. In this case report, we present a case of PAMM after a transient central retinal artery occlusion and the multifocal electroretinogram (mfERG) and other multimodal imaging findings. Clinical examination, OCT angiography, OCT en face , fluorescein angiography, and visual fields were performed at the baseline and follow-up examinations. As a result,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…6 In addition, some evidence revealed that the choriocapillaris may also be hypoperfused along with the deep capillary plexus in PAMM lesions. 7 Retinal changes 2.5-5 years after acute PAMM lesions include excavation of the inner retinal surface, inner nuclear layer thinning, and presence of abnormal vasculature in the deep capillary plexus. 8 The etiology of PAMM has not been clearly elucidated as causative factors range from the use of vasoconstrictors, such as caffeine, amphetamines, epinephrine, and oral contraceptives, to microvascular diseases, including hypertension, diabetes, and sickle cell disease.…”
Section: Discussionmentioning
confidence: 99%
“…6 In addition, some evidence revealed that the choriocapillaris may also be hypoperfused along with the deep capillary plexus in PAMM lesions. 7 Retinal changes 2.5-5 years after acute PAMM lesions include excavation of the inner retinal surface, inner nuclear layer thinning, and presence of abnormal vasculature in the deep capillary plexus. 8 The etiology of PAMM has not been clearly elucidated as causative factors range from the use of vasoconstrictors, such as caffeine, amphetamines, epinephrine, and oral contraceptives, to microvascular diseases, including hypertension, diabetes, and sickle cell disease.…”
Section: Discussionmentioning
confidence: 99%